2000
DOI: 10.1002/1521-3935(20001201)201:18<2676::aid-macp2676>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of novel fluorinated aliphatic polyurethanes with fluoro chain extenders

Abstract: Fluorinated aliphatic polyurethanes based on hexamethylene diisocyanate (HDI) and polytetramethyl oxide (PTMO) were synthesized by using 2,2,3,3,4,4,5,5‐octafluoro‐1,6‐hexanediol (OF) or 2,2,3,3‐tetrafluoro‐1,4‐ butanediol (TF) as a chain extender. The polyurethanes chainextended with 1,4‐butanediol (BD) were also prepared for comparison. The effects of the kind of chain extender and the average length of hard segments on the microstructure, thermal transition property, surface property and blood compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…In recent years, a number of the preparations of the FPUs have been reported 21–33. Some studies introduced fluorocarbon chains into PUs by hard segment, or diisocyanate to obtain new PUs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of the preparations of the FPUs have been reported 21–33. Some studies introduced fluorocarbon chains into PUs by hard segment, or diisocyanate to obtain new PUs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang found that the formation of stronger hydrogen bonds with an increase of the soft chain length led to an increase of the microphase separation and different thermal behaviors. Chen et al synthesized fluorinated polyurethanes with different hard‐segment lengths. Their research showed that the microphase separation, melting temperature and crystallinity in the hard segments increased with an increase of hard‐segment length.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low reaction activity of the fluorinated polyol leads to the low molecular weight and poor mechanical property of the resulting products, which may restrict the wide applications of fluorinated polyurethane (FPU). Moreover, compared to other polyols, the fewer species and quantities of the fluorinated polyol further limited their use as modifying monomers for fluorinated polyurethane [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%